2021
DOI: 10.1172/jci.insight.142513
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 blockade restores helper activity of tumor-infiltrating, exhausted PD-1hiCD39+ CD4 T cells

Abstract: Tumor antigen–specific CD4 T cells accumulate at tumor sites, evoking their involvement in antitumor effector functions in situ. Contrary to CD8 cytotoxic T lymphocyte exhaustion, that of CD4 T cells remains poorly appreciated. Here, using phenotypic, transcriptomic, and functional approaches, we characterized CD4 T cell exhaustion in patients with head and neck, cervical, and ovarian cancer. We identified a CD4 tumor-infiltrating lymphocyte (TIL) population, defined by high PD-1 and CD39 expression, which con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 35 publications
3
72
0
Order By: Relevance
“…Although the effects of ICI have been thoroughly explored in CD8 + T cells, the roles played by CD4 + T cells in response to ICI remain poorly understood. Balança et al studied exhausted CD4 + T cells in head and neck, cervical, and ovarian cancers [ 95 ]. With exhausted CD4 + T cells defined as those cells presenting high PD-1 and CD39 levels, which were found to secrete CXCL13 and express the transcription factor thymocyte selection-associated high mobility group box (TOX).…”
Section: The Expression and Implications Of Cxcl13/cxcr5mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effects of ICI have been thoroughly explored in CD8 + T cells, the roles played by CD4 + T cells in response to ICI remain poorly understood. Balança et al studied exhausted CD4 + T cells in head and neck, cervical, and ovarian cancers [ 95 ]. With exhausted CD4 + T cells defined as those cells presenting high PD-1 and CD39 levels, which were found to secrete CXCL13 and express the transcription factor thymocyte selection-associated high mobility group box (TOX).…”
Section: The Expression and Implications Of Cxcl13/cxcr5mentioning
confidence: 99%
“…Balança et al studied the role of CD4 + T cells in immunotherapy during the attack on cancer cells [ 95 ]. They applied single-cell RNA sequencing analysis to patient-derived samples of head and neck, cervical, and ovarian cancer to detect the expression of transcription factor TOX and the chemokine CXCL13.…”
Section: The Cxcl13/cxcr5 Signaling Axis In the Ici Response Of Preclinical Modelsmentioning
confidence: 99%
“… 33–35 More important in the setting of our study, they are essential for the development of Tfh cells and the induction of exhaustion in both CD4+ and CD8+ T cells. 36–41 Corresponding with our DEG, TOX can induce the expression of the Tfh defining chemokine CXCL13, and immune checkpoint molecule PD-1, which is a well-established marker of exhaustion. 42 , 43 Of note, in our immunohistochemistry analysis, T cells expressing TOX and/or TOX2 outnumbered cells expressing CXCL13 and PD-1, confirming a previous report that the exhaustion phenotype is a dominant feature in the cHL TME.…”
Section: Discussionmentioning
confidence: 91%
“…More recently, CD39 has been identified as a marker for tumor-specific CD4 + T cell population in human TILs suggesting that CD39 could be used to identify, isolate and expand tumor-reactive T cell population before ACT immunotherapy [ 183 ]. Since another team has demonstrated that this tumor-specific CD39 + CD4 + TILs population expresses CXCL13, PD-1 and TOX exhaustion makers and this population could contribute to tumor-specific CD8 + T cell proliferation and DC maturation through in situ reactivation with PD-1 blockade [ 184 ]. In addition to clinical and therapeutic success of TILs, several cytokines were used to enhance ACT efficacy and overcome immunosuppressive TME.…”
Section: Cd4 + T Cell Help For Cancer Immunotherapiesmentioning
confidence: 99%